A Study of Contextual Architectural Approaches in the Arrangement of Public Spaces in Enrekang City Park - Rusdin Jumurdin; Muhammad Uliah Shafar; Izharul Haq (Journal Of Architectural Design & Technology, 2025)
Enrekang City Park is one of the most popular public open spaces and has become a main destination for the community to engage in physical activities, relax, and socialize, both on weekdays and weekends. The presence of various facilities such as pedestrian pathways, children's play areas, and seating has supported the park’s function as a recreational space for the public. However, it is important to further examine whether the park has been designed with an approach that considers the environmental, social, and cultural context of Enrekang. Contextual architecture is an approach that emphasizes the relationship between design and both the physical and non-physical conditions of a region, including aspects such as culture, climate, topography, and user behavior. Through this approach, the city park is expected not only to serve as a functional green space, but also to reflect local identity and create comfort aligned with the character of the local community. This research aims to identify, analyze, and evaluate the extent to which the principles of contextual architecture have been applied in the layout of Enrekang City Park. Using a descriptive-qualitative method and a case study approach, this study will observe the park’s design elements from both physical and socio-cultural aspects that support the creation of a contextual public space. The results of this research are expected to provide input for planners, architects, and local governments in creating city parks that are aligned with local character and community needs.